2020
DOI: 10.1017/jfm.2020.153
|View full text |Cite
|
Sign up to set email alerts
|

Large-amplitude membrane flutter in inviscid flow

Abstract: We study the large-amplitude flutter of membranes (of zero bending rigidity) with vortex-sheet wakes in 2D inviscid fluid flows. We apply small initial deflections and track their exponential decay or growth and subsequent large-amplitude dynamics in the space of three dimensionless parameters: membrane pretension, mass density, and stretching modulus. With both ends fixed, all the membranes converge to steady deflected shapes with single humps that are nearly fore-aft symmetric, except when the deformations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 149 publications
8
45
0
Order By: Relevance
“…Recent works on membrane flutter are motivated by such diverse applications as stability of membrane roofs in civil engineering (Sygulski 2007), flutter of travelling paper webs (Banichuk et al 2010(Banichuk et al , 2019, aerodynamics of sails and membrane wings of natural flyers (Newman & Paidoussis 1991;Tiomkin & Raveh 2017), as well as the design of piezoaeroelastic systems for energy harvesting (Mavroyiakoumou & Alben 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recent works on membrane flutter are motivated by such diverse applications as stability of membrane roofs in civil engineering (Sygulski 2007), flutter of travelling paper webs (Banichuk et al 2010(Banichuk et al , 2019, aerodynamics of sails and membrane wings of natural flyers (Newman & Paidoussis 1991;Tiomkin & Raveh 2017), as well as the design of piezoaeroelastic systems for energy harvesting (Mavroyiakoumou & Alben 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The membrane and flow models are the same as in Mavroyiakoumou and Alben (2020) but we repeat them briefly for completeness. The membrane dynamics are described by the unsteady extensible elastica equation with body inertia, stretching resistance, and fluid pressure loading, obtained by writing a force balance equation for a small section of membrane that lies between material coordinates α and α + ∆α:…”
Section: Membrane and Vortex-sheet Modelmentioning
confidence: 99%
“…Membranes arise in various biological and technological applications including membrane aircraft and shape-morphing airfoils (Lian and Shyy, 2005;Hu et al, 2008;Stanford et al, 2008;Jaworski and Gordnier, 2012;Piquee et al, 2018;Schomberg et al, 2018;Tzezana and Breuer, 2019), sails (Colgate, 1996;Kimball, 2009), parachutes (Pepper and Maydew, 1971;Stein et al, 2000), membrane roofs (Haruo, 1975;Knudson, 1991;Sygulski, 1996Sygulski, , 1997Sygulski, , 2007, and the wings of flying animals such as bats (Swartz et al, 1996;Song et al, 2008;Cheney et al, 2015). The majority of previous studies of membranes showed that when they are held with their ends fixed in a uniform oncoming fluid flow, they tend to adopt steady shapes with a single hump (that is, when the flat state is unstable) (Song et al, 2008;Mavroyiakoumou and Alben, 2020). In the current work, we show that periodic and chaotic oscillations can occur in a simple physical setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many interesting phenomena in fluid mechanics occur as a result of the interaction of a fluid with solid or flexible structures. Most numerical algorithms to study such problems require discretizing the bulk fluid [5,35,75] or are tailored to the case of slender bodies [66], flexible filaments [4,52] or unbounded domains [30]. In the present paper, we propose a robust boundary integral framework for the fast and efficient numerical solution of the incompressible, irrotational Euler equations in multiply-connected domains that have numerous fixed obstacles, variable bottom topography, a background current, and a free surface.…”
Section: Introductionmentioning
confidence: 99%